Vancomycin Paste does not Reduce the Incidence of Deep Sternal Wound Infection after Cardiac Surgery - Lander, Heather L. (Ann Thorac Surg, 2016)
BACKGROUND: Deep sternal wound infection (DSWI) is a devastating complication that increases morbidity and mortality in cardiac surgery patients. Vancomycin is often administered intravenously for antibiotic prophylaxis in cardiac surgery. Many cardiac surgeons also apply vancomycin paste topically to the sternal edges. We examined the effect of vancomycin paste upon the incidence of DSWI in patients undergoing elective cardiac surgery. METHODS: We performed a single institution, retrospective medical record review of all patients from 2003 to 2015 who underwent CABG, valve or CABG/valve surgery. We derived the Society for Thoracic Surgeons (STS) DSWI risk index for each patient and performed a systematic review of operative, pharmacy, microbiology and discharge records to identify patients that developed DSWI. Multivariate analyses were used to identify predictors of DSWI in this cohort and to quantify the effect of vancomycin paste. RESULTS: 14,492 patients were examined, of whom 136 patients developed DSWI, resulting in an overall incidence of 0.9%. After multivariate analysis, body mass index, NYHA class and STS DSWI risk index remained statistically significant and associated with DSWI. Although the incidence of DSWI decreased over time, the use of vancomycin paste was not associated with a reduced incidence of DSWI. CONCLUSIONS: There was a marked decrease in the incidence of DSWI over the study period, concurrent with institutional implementation of revised STS antibiotic dosing guidelines in 2007 and other strategies. However, the application of vancomycin paste to the sternal edges of patients undergoing cardiac surgery was not associated with a reduced risk of DSWI.